COVID-19-Related Knowledge and Anxiety Among Health-Care Workers in a Tertiary Care Centre in Kerala. Issue 1 (June 2021) - K. P., Lakshmi; Prasanna, Preetha; Chandra, Subash; G. Krishnan, Arya; Babu, Abhinandh; Babu, Binil; Moni, Merlin; Sathyapalan, Dipu T.
Introduction: The COVID-19 pandemic has posed an immense threat to both physical as well as mental health globally. The outbreak is immeasurably affecting all the communities worldwide. The pandemic fatigue has led to inadequate addressing of the impact of COVID-19 on mental health especially among the health-care workers (HCWs), mainly due to the fear of disease contraction, mortality of the condition, raised work stress, as well as the saturation of news on media and other social platforms. Prolonged confinement at home may also adversely impact mental health. Method: An online survey was conducted using a developed questionnaire to evaluate the knowledge and anxiety among 118 HCWs regarding the COVID-19 pandemic in a tertiary care hospital. Since the study was conducted during the period in which no standard questionnaires were available, an online questionnaire was developed based on a few articles published in indexed journals on the similar topic which was further approved by 5 experts in the field. The questionnaire along with an informed consent was sent to all the HCWs employed in the hospital to assess their knowledge and anxiety related to COVID-19. Result: A total of 92.47% of participants were strongly aware that the major mechanism in COVID spread is droplet infection. An equal percentage of participants had good knowledge that the infection can always be prevented by maintaining social distance, appropriate hand washing, hand sanitizing, and using a mask. However, around 40.67% of participants avoided large meetings even in hospitals due to fear of the pandemic. Conclusion: It is important to study the mental health impacts of HCWs during the pandemic. There is a need to intensify the awareness program and address the mental health issues of HCWs during this COVID-19 pandemic.